Trends and Perspective of Metabolic Syndrome - Nnodim Johnkennedy; Njoku-Obi Treasure; Ikem Amarachi Promise (Newinera Publisher, 2022)
Overweight, sedentary lifestyles, and some degree of insulin resistance are only a few of the traits linked with individuals who have the metabolic syndrome. Additional risk factors include a sedentary or inactive lifestyle, the use of psychiatric drugs, and excessive alcohol use. Weight gain and insulin resistance are connected with the metabolic syndrome. The most effective methods of losing weight are low-calorie diets and increased physical activity. Preliminary research indicates that individuals who consume a paleolithic diet may reduce three of the five quantitative risk factors for cardiovascular disease.